Chemical constituents from the fresh flower buds of Musa nana and their chemotaxonomic significance. (December 2021) - Tang, Minmin; Zhou, Xueming; Cai, Jin; Chen, Guangying
Abstract: Phytochemical study on the fresh flower of Musa nana Lour. provided seventeen known compounds including two alkaloids, 3-(hydroxyacetyl)-indole (1 ), bi-indol-3-yl (2 ), two terpenoids, 5-[(1 R )-1-hydroxy-2, 6, 6-trimethyl-4-oxo-2-cyclohexen-1-yl]-3-methyl-, (2 Z, 4 E ) −2, 4-pentadienoic acid (Valdes), 5, 6( S ), 7, 7a( R )-tetrahydro-6-hydroxy-4, 4-dimethyl-2(4 H )-benzofuranone (4 ), seven phenols (5 –11 ), three phenylphenalenones, 2-hydroxy-4-(4-methoxyphenyl)-1 H -phenalen-1-one (12 ), 2-methoxy-9-phenyl-1 H -phenalen-1-one (13 ), 2-methoxy-9-(4-methoxyphenyl)-1 H -phenalen-1-one (14 ), and three lipids (15 –17 ). In the present study, all the compounds were isolated for the first time from the species M. nana . Ten compounds including 1-8 and 15-16 have never been previously encountered in the Musaceae family. Furthermore, the chemotaxonomic significance of these isolates was also discussed. Highlights: Seventeen compounds were isolated from Musa nana Lour. for the first time. Ten compounds were isolated from the family Musaceae for the first time. Chemotaxonomic significance of these compounds was discussed.